1997
DOI: 10.1074/jbc.272.42.26346
|View full text |Cite
|
Sign up to set email alerts
|

A New Action of Parathyroid Hormone

Abstract: The major physiological function of parathyroid hormone (PTH) is the maintenance of Ca 2؉ /P i homeostasis via the parathyroid hormone/parathyroid hormone-related protein receptor (PTHR) in kidney and bone. An important consequence of PTHR activation in bone is enhanced local acidification of the extracellular space. Agonist activation of some seven transmembrane-domain receptors increases the extracellular acidification rate (ECAR). We utilized microphysiometry to investigate PTH-stimulated, receptor-mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…Only the latter is positively regulated by INSL3 and these data again well agree with our previous experiments on Rxfp2 −/− mice [4], as PTH stimulates osteoclast-mediated bone resorption indirectly via the activation of the PTHR on osteoblasts [42].…”
Section: Discussionsupporting
confidence: 92%
“…Only the latter is positively regulated by INSL3 and these data again well agree with our previous experiments on Rxfp2 −/− mice [4], as PTH stimulates osteoclast-mediated bone resorption indirectly via the activation of the PTHR on osteoblasts [42].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, Esen et al, provided evidence that the majority of the increase in glucose uptake with PTH treatment is mediated through PKA signaling. Conversely, other studies in human SaOS-2 and rat osteoblast like UMR-106 cells have shown that the increased glycolysis with PTH (1–34) treatment is mostly mediated by PKC signaling, independent of cAMP/PKA and Na+/H+ exchanger pathways ( Barrett et al, 1997 ; Belinsky et al, 1999 ; Belinsky and Tashjian Jr., 2000 ). Alternatively, another study using MC3T3E1C4 cells showed that PTH treatment enhanced osteoblast differentiation through GPR81-Gβγ-PLC-PKC-Akt signaling coupled with increased lactate production ( Wu et al, 2018 ).…”
Section: Discussionmentioning
confidence: 84%
“…The Cytosensor microphysiometer (Hafner, 2000) was widely adopted in the late 90s to measure metabolic changes and was particularly relevant for APJ deorphanization. This technology provides a quantitative measurement of extracellular acidification rate elicited by small molecules, neuropeptides, and hormones in response to GPCR activation but also to ligand-gated ion channels and receptor tyrosine kinases (Barrett et al, 1997;Lang et al, 2001;Merkouris et al, 1997;Ng et al, 2001;Pitchford et al, 1995;Pitchford et al, 1997).…”
Section: Apelin/elabela Receptor (Apj Receptor)mentioning
confidence: 99%